Riqueza de espécies de Oligochaeta (Annelida, Clitellata) em duas represas do rio Tietê (São Paulo). - Pamplin, Paulo Augusto (2005)
The species richness of Oligochaeta was evaluated in two reservoirs belonging to Tieté River System, Bariri and Ponte Nova Reservoirs. 360 sediment samples were taken in each reservoir at 90 sampling stations using a Van Veen grab (378 cm2), in the months January, April, July and October 2001. A total of 12.826 oligochaete specimens were collected, belonging to 20 species, 10 genera and 4 families. The family and genus with the highest species richness were Naididae and Dero, with 14 and 9 species, respectively. Among all species identified 6 occurred in both reservoirs, being Branchiura sowerbyi (Tubificidae) the most abundant species in them. The study also revealed that most Oligochaeta species are rare and have accidental occurrence, thus evidencing that for a better knowledge of species richness is actually necessary a great  sampling effort including a large number of sampling points.